LABOUR AND SOCIAL SECURITY IN THE THIRD MILLENNIUM – THE TOUCHSTONE OF THE KNOWLEDGE SOCIETY - Claudia-Ana MOARCĂȘ (Challenges of the Knowledge Society)
The end of the world’ has been predicted in many ways: one claimed the conscious robots would turn against the humans. ‘The end of the world as we know it’ is less murderous, yet worrying enough, because it means a radical change in one of man’s defining features: labour, with the Fourth Industrial Revolution as one of its causes. Structural challenges to the labour environment and tools set the background for this development. Labour’s fundamental components like who is performing it; how its results impact on the human being that performs it; and what laws must govern the interactions among labourers and society are all subject to change hereafter. The increasing role of technology, knowledge-based economy, and the continuous diversification of man’s needs and aspirations to safeguard the paramount human dignity outline the mandatory demand of adapting the labour law and social security law to these developments. Automation and robotisation are unavoidable and are to be implemented by continuously observing said needs and aspirations. Competence and ever higher levels of professionalism are mandatory for present and future lawyers and legislators in this domain.